Environmental Protection: Need to Comply with Environmental Impact Assessment Act to Curb Indiscriminate Telecommunication Mast Installation in Nigeria - Kehinde, Adeola Olufunke (PRAWO i WIĘŹ, 2022)
Environmental protection is non-negotiable in any part of the world, governments and relevant stakeholders should ensure that the lives of citizens are not put at unnecessary risk because of a lack of adequate environmental protection, thus, people should live in a safe and healthy environment. The author focuses on the environmental protection of residents in Nigeria since it especially affects telecommunication installation in the country. The telecommunication industry in Nigeria is fast growing over time and it has been discovered that as the industry grows, the aspect of environmental protection as it affects Environmental Impact Assessment of such installation has been neglected, thus, affecting the public health of residents in Nigeria as will be revealed in this paper. The author brings out the need to properly regulate the telecommunication sector to guarantee environmental protection for Nigerian residents.